Tegoprazan and low- or high-dose amoxicillin dual therapy versus bismuth-containing quadruple therapy for eradication (TREAT): protocol for a multicenter, open-label, non-inferiority, randomized controlled trial - Yi Hu; Xin Xu; Cong He; Nian-Shuang Li; Yong Xie; Xu Shu; Nong-Hua Lu; Yin Zhu (Therapeutic Advances in Gastroenterology)
Background: Recently, tegoprazan was widely used for the treatment of acid-related diseases, including Helicobacter pylori ( H. pylori ) infection. However, the optimized parameters of tegoprazan and amoxicillin used in dual therapy for eradicating H. pylori remained unresolved. Objectives: We mainly aim to compare the efficacy and safety of 14-day tegoprazan and low-dose amoxicillin dual therapy (LTA) or high-dose amoxicillin dual therapy (HTA) with 14-day bismuth-containing quadruple therapy (BQT) as first-line treatment of H. pylori infection. The antibiotic resistance and the impacts of therapy on gut microbiota are also evaluated. Design: Study protocol for a multicenter, open-label, non-inferiority, randomized controlled trial. Methods and analysis: This trial will recruit H. pylori -infected individuals aged 18–70 years without previous eradication. Participants will be randomized in a 1:1:1 ratio to LTA (amoxicillin 1 g twice a day and tegoprazan 50 mg three times daily), HTA (amoxicillin 1 g and tegoprazan 50 mg both three times daily), or BQT (amoxicillin 1 g, clarithromycin 500 mg, esomeprazole 20 mg, and bismuth potassium citrate 220 mg all twice daily) for 14 days using block size of 6. Stool samples will be collected at baseline to detect antibiotic resistance and at baseline, week 2, and weeks 8–10 to evaluate the alteration of gut microbiota. The primary outcome is the eradication rate of H. pylori , assessed by 13 C urea breath test, in intention-to-treat, modified intention-to-treat, and per-protocol analyses. Secondary outcomes include adverse events, adherence, antibiotic resistance, and alterations to the gut microbiota. Ethics: This study has been approved by the Ethics Committee of the First Affiliated Hospital of Nanchang University (No. 2024150-2). Ethics approval of each participating center is required before initiation of enrollment. Written informed consent to participate will be obtained from all participants. Discussion: This is the first study to investigate the safety and efficacy of 14-day tegoprazan with different dosages of amoxicillin therapies in comparison with BQT. The outcomes of this study will optimize the use of tegoprazan dual therapy for H. pylori eradication. Trial registration: The trial was registered on the Chinese Clinical Trial Registry (ChiCTR2400089979) on 20th September 2024.